An Analysis of Tax Court Decisions in Branch Profit Tax (BPT) Disputes in the Oil and Gas Sector Related to Production Sharing Contracts (PSCs) Toward Legal Certainty in Indonesia - Haryono Haryono; Jafar Chan (International Journal Labs, 2026)
Several Tax Court decisions regarding Branch Profit Tax disputes involving Oil and Gas Contractors demonstrate inconsistent rulings for identical BPT disputes concerning the relationship between national tax provisions and the Production Sharing Contract regime. This inconsistency in rulings for similar disputes can be viewed as an indication of legal uncertainty in terms of law enforcement within the Tax Court. This study aims to analyze the legal considerations underlying Tax Court decisions in BPT disputes related to PSCs in the oil and gas sector and to evaluate how these decisions reflect and contribute to the realization of legal certainty in Indonesia's taxation system. This research employs normative legal methods through statutory, conceptual, and case approaches by analyzing several Tax Court decisions related to Oil and Gas BPT disputes. The research results indicate that there are fundamental differences in the application of legal interpretation methods by the panels of judges. Furthermore, some panels of judges emphasize the principle of legality and formal legal certainty, while others prioritize substantive interpretation that considers contractual justice within the PSC. These differing legal approaches result in inconsistent rulings, thereby creating ambiguity in the application of BPT and undermining legal certainty. To achieve equitable legal certainty, it is necessary to harmonize regulations between the Income Tax Law and PSC provisions, establish jurisprudential guidelines, and enact amendments to ensure clearer drafting of PSCs.